Answer:
y - 6 = -7(x - 3)
General Formulas and Concepts:
Pre-Algebra
- Order of Operations: BPEMDAS
Algebra I
Slope Formula:
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e9lgdayfzr27dyurvzbw9lffpiv7535tiv.png)
Point-Slope Form: y - y₁ = m(x - x₁)
Explanation:
Step 1: Define
Point (3, 6)
Point (5, -8)
Step 2: Find slope m
- Substitute:
![m=(-8-6)/(5-3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/kztca3bq6q5ptj3zbyqyzfzvcplbz2h7ae.png)
- Subtract:
![m=(-14)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/rag8vd6kuh43b5y64zkceapuuq23n8ptq5.png)
- Divide:
![m=-7](https://img.qammunity.org/2021/formulas/mathematics/high-school/mulcovjlmac644f6w15o5junaoz1zcuv9n.png)
Step 3: Write equation
Point (3, 6)
Slope m = -7
y - 6 = -7(x - 3)